CONSIDERATIONS CONCERNING THE EVALUATION OF TOWING FORCES FOR ROAD TRANSPORTATION OF AGABARITICAL MECHANICAL EQUIPMENT - RADU IATAN; MIHAI STATESCU; ION DURBACA; GEORGIANA LUMINITA ENACHESCU (Journal of Engineering Studies and Research)
The full safety of operating industrial mechanical equipment, in particular the over-sized ones, with a complex structure, is ensured by compliance with all necessary requirements, starting with design, fabrication, transportation from the supplier to the recipient and operation within the working parameters. The present article that is continuing the analysis of transportation stages of over-sized and heavy equipment, as can be seen from the attached bibliography, takes into consideration the evaluation of the towing forces, in the case of two distant platforms. The masses of the transported components, the characteristics of the roadways, as well as the character of the movement and the influence of the wind loads are considered.